Bone Marrow Aspiration Does Not Induce a Measurable Pain Response Compared to Sham Procedure - Rowland, Aileen L.; Navas de Solis, Cristobal; Lepiz, Mauricio A.; Cummings, Kevin J.; Watts, Ashlee E. (Frontiers in Veterinary Science, 2018)
Bone marrow is commonly collected from horses for regenerative medicine applications. Little information is available regarding pain experienced by the horse during bone marrow aspiration. The objective of this study was to characterize horse reaction and pain response during bone marrow aspiration (BMA) compared to a sham (SHAM) procedure. We hypothesized there would be significantly greater horse reaction or pain response measured by salivary cortisol, heart rate variability, and depth and duration of sedation measured by sedation scores and head height between BMA and SHAM. Twelve university owned horses underwent a BMA and sham procedure, four weeks apart in a randomized cross-over design, while sedated with 0.4 mg/kg xylazine hydrochloride. As measures of sedation depth, head height was recorded and sedation level was scored at specific procedural time points. Salivary cortisol was measured immediately before and two hours after each procedure. Heart rate variability was assessed before, during, and after each procedure. There were no differences in head height, sedation score or salivary cortisol between groups. No differences were noted between groups in heart rate variability before or during the procedure, but there was a significant decrease in low frequency/high frequency (LF/HF) ratio after the procedure in the BMA group. Over time, there was a significant reduction in LF/HF ratio during the procedure in both groups. Overall, BMA from the sternum did not result in a measurable pain response during, or in the 2 hours following the procedure, in comparison to a sham procedure.